Una propedeutica della perplessità: “crisi” e negoziazione della “presenza” nelle novelle di Gianni Celati - Rea, Elisabetta (Status Quaestionis, 2023)
Starting in the mid-1980s, Gianni Celati returned to narrative with the genre of the short story, which would remain his chosen one for the rest of his narrative production. In the present contribution, Celati’s short stories are analysed in synchrony and on the basis of an illuminating comparison with the text by an author dear to Celati, Ernesto De Martino’s Il mondo magico. The key of psychopathology, with which Celati’s characters are usually analysed, may be limiting when compared with the Demartinian notion of the “crisis of presence”, which this study attempts to apply to the world of the author’s short stories, highlighting how, in an ideal step-by-step path, from the moment of rupture and crisis one arrives at the renegotiation of one’s presence in the world.